식물의 감수분열에서 상동 재조합 효소 특이 기능의 연구현황 및 전망 - 정유진(Yu Jin Jung); 남기홍(Ki Hong Nam); 김태성(Tae Sung Kim); 이인혜(In Hae Lee); 조용구(Yong-gu Cho); 강권규(Kwon Kyoo K (Journal of plant biotechnology, 2018)
Meiosis is a specialized cell division, essential in most reproducing organisms to halve the number of chromosomes, thereby enabling the restoration of ploidy levels during fertilization. A key step in meiosis is homologous recombination, which promotes homologous pairing and generates crossovers (COs) to connect homologous chromosomes until their separation at anaphase I. These CO sites, seen cytologically as chiasmata, represent a reciprocal exchange of genetic information between two homologous non-sister chromatids. RAD51, the eukaryotic homolog of the bacterial RecA recombinase, plays a central role in homologous recombination (HR) in yeast and animals. Loss of RAD51 function causes lethality in the flowering plant, Arabidopsis thaliana, suggesting that RAD51 has a meiotic stage-specific function that is different from homologous pairing activity.